Clinical Investigation on the Impact of Cannabis Abuse on Thyroid Hormones and Associated Psychiatric Manifestations in the Male Population - Muzaffar, Anum; Ullah, Sami; Subhan, Fazal; Nazar, Zahid; Hussain, Syed Mehdi; Khuda, Fazli; Khan, Abuzar; Khusro, Ameer; Sahibzada, Muhammad Umar Khayam; Albogami, Sarah; El-Shehawi, Ahmed M.; Emran, Talha Bin; et al. (Frontiers in Psychiatry, 2021)
Cannabis abuse is a common public health issue and may lead to considerable adverse effects. Along with other effects, the dependence on cannabis consumption is a serious problem which has significant consequences on biochemical and clinical symptoms. This study intends to evaluate the harmful effects of the use of cannabis on thyroid hormonal levels, cardiovascular indicators, and psychotic symptoms in the included patients. This prospective multicenter study was conducted on cannabis-dependent patients with psychotic symptoms (n = 40) vs. healthy control subjects (n = 40). All participants were evaluated for psychiatric, biochemical, and cardiovascular physiological effects. Patients were selected through Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV criteria and urine samples, exclusively for the evaluation of cannabis presence. Serum thyroid stimulating hormone (TSH), T3, and T4 levels were measured using the immunoassay technique. Patients were assessed for severity of depressive, schizophrenic, and manic symptoms using international ranking scales. Various quantifiable factors were also measured for the development of tolerance by cannabis. Among the patients of cannabis abuse, 47.5% were found with schizophrenia, 20% with schizoaffective symptoms, 10% with manic symptoms, and 22.5% with both manic and psychotic symptoms. In the group–group and within-group statistical analysis, the results of thyroid hormones and cardiovascular parameters were non-significant. The psychiatric assessment has shown highly significant (p < 0.001) difference of positive, negative, general psychopathology, and total scores [through Positive and Negative Syndrome Scale (PANSS) rating scales] in patients vs. the healthy control subjects. The study revealed that cannabis abuse did not significantly alter thyroid hormones and cardiovascular parameters due to the development of tolerance. However, the cannabis abuse might have a significant contributing role in the positive, negative, and manic symptoms in different psychiatric disorders.